Case study company analysis: Pokok Twin / Nurjeha Ramli ... [et al.] - Ramli, Nurjeha; Zakaria, Nurul Izzati; Zanil Abaddin, Siti Zulaikha; Abdullah, Fatin Nurshahirah Iwana; Mohd Riffin, Muhammad Arif Aiman (2021)
The overview of this case is that we were able to identify the problem that have been slowing down her business even though the brand has been operating for 5 month. The business that we took as our research for assessment case study ENT530 is Pokok Twin by Manal Bin Usamah located at Taman Merbau Changloon Kedah. This Business sale products indoor and outdoor plants. The purpose of this case study are to describe and get more information about one of Malaysia entrepreneur and the business that she worked for the sake of knowledge and good example. Other than that, this case study are full of research about how she manage the business and the company SWOT analysis of the company, SWOT are actually strength, weakness, opportunities and threats of the company that can help the owner to avoid making costly mistakes and determine which product are most likely to succeed. It seems simple, but the result can contributes largely for the company to understand their usage of resources whether it leads to wastage or not. After all, a business cannot expand if their weaknesses overthrow their enhancement effort. Through our study, we discovered the company is having few problem. Therefore, few alternative solution, had been given by us for this business.